The nursing work environment and quality of care: Content analysis of comments made by registered nurses responding to the Essentials of Magnetism II scale. Issue 3 (9th April 2019) - Oshodi, Titilayo O.; Bruneau, Benjamin; Crockett, Rachel; Kinchington, Francia; Nayar, Shoba; West, Elizabeth
Abstract: Aim: To report a qualitative study of themes Registered Nurses raised spontaneously about their work environment, in a cross‐sectional survey study when responding to the Essentials of Magnetism II (EOMII) scale. Design: Qualitative descriptive survey. Methods: At the end of the EOMII scale, a free form text section was included asking nurses to add comments about their ward/work environment . Of the 247 nurses who completed the EOMII scale, 30% ( N = 75) provided comments. Inductive content analysis was used to analyse the textual information generated. Results: Three key themes emerged: "nurses need nurses to nurse"; working as a team and workplace environment. Participants described issues they were facing which comprised high turnover rates, inadequate staffing levels, increasing workload and high stress levels. Particular attention was drawn to the role of the ward manager in promoting a positive work environment, good teamwork and quality patient care.